2016
DOI: 10.1002/14651858.cd011052.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide-based versus nitrous oxide-free general anaesthesia and accidental awareness during general anaesthesia in surgical patients

Abstract: It is not possible to draw any conclusions from this review. The included studies were mainly small (fewer than 120 participants) and there were limited estimates of effect, with only two studies reporting any events. We cannot therefore determine whether the use of nitrous oxide in general anaesthesia increases, decreases or has no effect on the risk of accidental awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Inadequate glottic view accounted for 17 of 23 instances in which patients did not receive the intended intervention . Prior studies have indicated that difficulty, multiple attempts, or delay during tracheal intubation underpin many cases of airway misadventure, and systematic review indicates that video laryngoscopy improves ease and success of tracheal intubation, particularly if there is anatomical difficulty . The present study reinforces the vital importance of glottic visualization and the value of video laryngoscopy.…”
supporting
confidence: 62%
“…Inadequate glottic view accounted for 17 of 23 instances in which patients did not receive the intended intervention . Prior studies have indicated that difficulty, multiple attempts, or delay during tracheal intubation underpin many cases of airway misadventure, and systematic review indicates that video laryngoscopy improves ease and success of tracheal intubation, particularly if there is anatomical difficulty . The present study reinforces the vital importance of glottic visualization and the value of video laryngoscopy.…”
supporting
confidence: 62%
“…TIVA has been identified as a risk for intraoperative awareness and could contribute to a delayed emergence due to the inability to monitor plasma levels after its termination . Although it has been suggested that the inclusion of N 2 O reduces the incidence of intraoperative awareness, a recent Cochrane review could not conclusively corroborate those data . However, the ability to monitor an expired end tidal anesthetic concentration of 70% minimum alveolar concentration (MAC) was superior compared to Bispectral Index (BIS) monitoring to reduce intraoperative awareness .…”
Section: Discussionmentioning
confidence: 99%
“…A protocol for conducting this systematic review and the full published review are available elsewhere. We considered all RCTs including quasi‐randomised studies and cluster‐randomised studies.…”
Section: Methodsmentioning
confidence: 99%